2011
DOI: 10.1073/pnas.1106259108
|View full text |Cite
|
Sign up to set email alerts
|

Marriage exchanges, seed exchanges, and the dynamics of manioc diversity

Abstract: The conservation of crop genetic resources requires understanding the different variables-cultural, social, and economic-that impinge on crop diversity. In small-scale farming systems, seed exchanges represent a key mechanism in the dynamics of crop genetic diversity, and analyzing the rules that structure social networks of seed exchange between farmer communities can help decipher patterns of crop genetic diversity. Using a combination of ethnobotanical and molecular genetic approaches, we investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 35 publications
4
77
0
8
Order By: Relevance
“…Previous studies have shown that farmers' seed sharing networks drive the gene flow of crops within a region [9,17,18,50]. Access to diverse crop germplasm requires that farmers have adequate income or connections without social or political constraints to acquire different crop varieties [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that farmers' seed sharing networks drive the gene flow of crops within a region [9,17,18,50]. Access to diverse crop germplasm requires that farmers have adequate income or connections without social or political constraints to acquire different crop varieties [51].…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood groups [9] and marriage exchanges are other social factors that shape crop diversity at local and regional levels [16][17][18][19].…”
mentioning
confidence: 99%
“…Previous studies have acknowledged the role of traditional knowledge and culture practices of smallholder farmers and indigenous communities for biodiversity conservation at the species, genetic, ecosystem, and landscape levels (Altieri, 2004). Many traditional management practices, customs, and beliefs have been reported to contribute to biodiversity protection including seed exchange systems (Labeyrie, Thomas, Muthamia, & Leclerc, 2016), marriage exchanges (Delêtre, McKey, & Hodkinson, 2011), religious rituals (Mazumdar & Mazumdar, 2012), and dietary traditions (Penafiel, Lachat, Espinel, Van Damme, & Kolsteren, 2011). These practices, customs, and beliefs have been linked to preserving crop landraces (Jackson, Pascual, & Hodgkin, 2007), old trees (Salick et al., 2007), and economic plants (Liu et al., 2014) including those with esthetic, food, and medicinal values (Begum et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…operating at finer scales. On-farm management of crop varieties and cultural boundaries influencing the diffusion of seeds, practices, and knowledge are important local-scale explanatory factors behind patterns of regional and continental scale associations between ethnolinguistic groups and crop genetic structure (27)(28)(29)(30).…”
mentioning
confidence: 99%